Inadvertent intrathecal injections and best practice management. Issue 1 (21st October 2016) - Liu, H.; Tariq, R.; Liu, G. L.; Yan, H.; Kaye, A. D.
Abstract : The intrathecal space has become an important anatomic site for medical intervention not only in anesthesia practice, but also in many other medical specialties. Undesired/inadvertent intrathecal injections (UII) are generally rare. There is tremendous variation in reported inadvertent administrations via an intrathecal route in the literature, mainly as individual cases and very small case‐series reports. This review aims to identify potential sources of UII, its clinical presentations, and appropriate management. The inadvertent injectants are classified as anesthetic agents and pain medicines, chemotherapeutics, radiological contrast agents, antibiotics and corticosteroids, and miscellaneous chemical agents such as tranexamic acid. The clinical effects of UII are dependent upon inadvertent injectant(s) and dose being administered intrathecally, and can range from no adverse effect to profound neurological consequences and/or death. Prompt cerebrospinal fluid (CSF) lavage and cardiopulmonary support seem to be the mainstay of treatment. If serious consequences are anticipated, CSF lavage could be lifesaving. This review additionally provides some options for comprehensive management and preventing strategies.